PERAN PEMERINTAH DALAM MENINGKATKAN KESEJAHTERAAN PETANI SALAK DI DESA TINJOMAN LAMA KECAMATAN PADANGSIDIMPUAN HUTAIMBARU KOTA PADANG SIDIMPUAN TAHUN 2014 - Wicaksono, Baskoro (Nakhoda: Jurnal Ilmu Pemerintahan, 2016)
This research was conducted in the village of Tinjoman Lama District of PadangsidimpuanHutaimbaru Padangsidimpuan City with three research question How are the government?srole in improving welfare of farmers in the village barking Tinjoman Lama? The purpose ofthis study to determine government?s role in improving the welfare of farmers in the villagebarking Tinjomam Lama District of Padangsidimpuan Hutaimbaru Padangsdimpuan City. Thisstudy is a descriptive quantitative research. The population in this study were all barking farmersin the village of Tinjoman Lama. The sample of this study a total of 36 respondents (50%) ofthe overall polpulations using random sampling technique, that is by knowing all the farmersbarking then randomized based on the name for the next interview. To collect the data theresearchers use methods of document , observation and interview by using the interview guideas a reference to obtain information in analyzing the research data used quantitative analysisand descriptive described. Based on the study concluded lack of government?s role in improvingthe welfare of farmers bark that can be seen from the absence of assistance in the form ofmarketing, production quality improvement, education / training in agriculture, provision ofquality seeds and fertilizers or appropriate technology.